PHILOSOPHY EDUCATION FOR CHILDREN - Damar Prasetya (Undiksha, 2020)
Fundamentals of all subjects in higher university education were being taught since early childhood. The basic concepts of biology, medicine and physics were mandatory introduced as natural sciences subjects (ilmu pengetahuan alam) in elementary school curriculum as well as social sciences (ilmu pengetahuan sosial), languages and even religion. These early introduction of subjects will make sure that every children are exposed to this particular education to enrich their knowledge and skill. However, philosophy is not formally available in national curriculum until university level. Paradoxically, one of the essence of philosophy is to ensure a human being is capable to perform critical thinking in their later life. This review aims to delineate the urgency and benefit of introducing philosophy in children in either formal or informal form of education. The early introduction of philosophy will nurture and sharpen the process of thinking in children thus will help them to become a wiser adult in the future. This concept might be a consideration of inserting philosophy as one of the subject in national curriculum.